Predictive Value of the Magnetic Resonance Imaging–Based Coronal Lateral Collateral Ligament Sign on Adolescent Anterior Cruciate Ligament Reconstruction Graft Failure. Issue 4 (March 2021) - Mitchell, Brendon C.; Siow, Matthew Y.; Bastrom, Tracey; Bomar, James D.; Pennock, Andrew T.; Parvaresh, Kevin; Edmonds, Eric W.
Background: The coronal lateral collateral ligament (LCL) sign is the presence of the full length of the LCL visualized on a single coronal magnetic resonance imaging (MRI) slice at the posterolateral corner of the knee. The coronal LCL sign has been shown to be associated with elevated measures of anterior tibial translation and internal rotation in the setting of anterior cruciate ligament (ACL) tear. Hypothesis: The coronal LCL sign (with greater anterior translation, internal rotation, and posterior slope of the tibia) will indicate a greater risk for graft failure after ACL reconstructive surgery. Study Design: Cohort study; Level of evidence, 3. Methods: Retrospective review was performed of adolescent patients with ACL reconstruction: a cohort without graft failure and a cohort with graft failure. MRI was utilized to measure tibial translation and femorotibial rotation and to identify the coronal LCL sign. The posterior tibial slope was measured on lateral radiographs. Patient-reported outcomes were collected. Results: We identified 114 patients with no graft failure and 39 patients with graft failure who met all criteria, with a mean follow-up time of 3.5 years (range, 2-9.4 years). Anterior tibial translation was associated with anterolateral complex injury ( P < .001) but not graft failure ( P = .06). Internal tibial rotation was associated with anterolateral complex injury ( P < .001) and graft failure ( P = .042). Posterior tibial slope was associated with graft failure ( P = .044). The coronal LCL sign was associated with anterolateral complex injury ( P < .001) and graft failure ( P = .013), with an odds ratio of 4.3 for graft failure (95% CI, 1.6-11.6; P = .003). Subjective patient-reported outcomes and return to previous level of sport were not associated with failure. Comparison of MRI before and after ACL reconstruction in the graft failure cohort demonstrated a reduced value in internal rotation ( P = .003) but no change in coronal LCL sign ( P = .922). Conclusion: Our study demonstrates that tibial internal rotation and posterior slope are independent predictors of ACL graft failure in adolescents. Although the value of internal rotation could be improved with ACL reconstruction, the presence of the coronal LCL sign persisted over time and was predictive of graft rupture (without the need to make measurements or memorize values of significant risk). Together, these factors indicate that greater initial knee deformity after initial ACL tear predicts greater risk for future graft failure.